Biochar and chicken manure improve soil chemical properties and nutritional status of rosewood seedlings grown in clay soil - Cavalcante-Ferreira, João Cleber; Pereira-dos-Santos, Ana Beatriz; Pereira-Ribeiro, Rubia; da-Silva-Ribeiro, Heitor Marcel; Batista-Aoki, Rafaelle; Monteiro-de-Oliveira, Danielle; de-Souza-Falcão, Newton Paulo (Bosque (Valdivia), 2024)
Studies on the effects of biochar and chicken manure on soil chemical properties and initial growth of rosewood under field conditions in the Amazon are rare; therefore, a field experiment was carried out to evaluate the effects of biochar, chicken manure, and mineral fertilizer on the chemical properties of the soil, nutrient concentrations in the leaves, and on the initial growth of rosewood (Aniba rosaeodora) grown in clayey soil. The study was conducted in causal blocks, with five treatments (control, biochar, biochar plus chicken manure, biochar plus mineral fertilizer, and biochar plus chicken manure plus mineral fertilizer) and three replications. In general, we observed that the application of biochar and chicken manure, alone or in combination, increased soil pH, calcium, phosphorus, zinc, and manganese content, as well as foliar potassium and calcium concentrations. However, despite fertilization, we did not observe significant gains in the growth of A. rosaeodora seedlings until ten months after planting. The combination of biochar and chicken manure exhibited the greatest impact, and is therefore important for soil sustainability and plant development in tropical soils.